Analisa Efektivitas Dan Efisiensi Pompa Bravo Tipe WP20CX Untuk Pembersihan Kolam Renang di Kolam Rahayu Park - Mochammad Alim Huda; Mulyadi Mulyadi (Universitas Muhammadiyah Sidoarjo, 2018)
Technological development is very rapid, the demand for the needs of both goods and services is demanded to be faster. Pumps are one of the tools that are often used in industry to help meet human needs, where this tool is used to ease the burden of humans who cannot be demanded to continue working. But in determining the pump there are many things that need to be considered in its use. Analysis of the WP20CX BRAVO pump used in the process of assisting the provision of clean water in the Rahayu Park pond is one of the stages in which the performance of the pump is known in terms of the effectiveness and efficiency of the pump against pool cleaning. This determination was reviewed through several different discharge variables when taking 5 samples at each suction of 100%, 80%, 60% and 40% with the aim that the pump works optimally. From the discharge, the pump size is produced with a discharge of 300 liters / minute, pump diameter 2